2014
DOI: 10.1016/j.juro.2014.06.079
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Urine Cytology Stain for the Detection and Monitoring of Bladder Cancer

Abstract: Findings show the capability of CellDetect to accurately identify urothelial carcinoma. This indicates that the technology can be further developed to provide an alternative urine cytology test with diagnostic value that may have significant clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…In addition, the CellDetect assay is a novel histochemical staining platform which allows for the discrimination between normal and malignant cells on the basis of color and morphological discrimination-based on the higher metabolic activity in cancer cells [39]. An Israeli study across 9 hospitals employing urine smears found that the overall sensitivity of this test was 84%, and the specificity was also 84% for patients undergoing routine surveillance by cystoscopy [40].…”
Section: Additional Protein Markers Detectable In the Urinementioning
confidence: 99%
“…In addition, the CellDetect assay is a novel histochemical staining platform which allows for the discrimination between normal and malignant cells on the basis of color and morphological discrimination-based on the higher metabolic activity in cancer cells [39]. An Israeli study across 9 hospitals employing urine smears found that the overall sensitivity of this test was 84%, and the specificity was also 84% for patients undergoing routine surveillance by cystoscopy [40].…”
Section: Additional Protein Markers Detectable In the Urinementioning
confidence: 99%
“…13,14 There are only a few studies on its efficacy in bladder TCC detection. In the preliminary study in 2014, Davis et al 11 showed that this method has 94% sensitivity and 89% specifity in 44 urine samples, particularly in low grade tumors. In 2018, a multicentric study by the same author showed that the overall sensitivity of CellDetect ® was 84% in 217 urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…Normal bladder cells and TCC stain differently with CellDetect ® and can be differentiated morphologically. 10,11 The target of the stain is the cell nucleus. Benign epithelial cells are stained in greenish tones while malign cells are stained in red and its tones.…”
Section: Introductionmentioning
confidence: 99%
“…the bladder tumour-associated antigen (BTA) TRAK assay, nuclear matrix protein 22 (NMP22) and uCyt1 tests, have been approved by the United States Food and Drug Administration (FDA) but their utility is still very limited [15]. None of them have been incorporated in guidelines [16][17][18] and suffer from low sensitivity, especially for LGTs [19]. To improve cytology performance, new techniques have been also tested for harvesting intact urinaryexfoliated tumour cells, but the economic impact is high and the gain in term of sensitivity remains poor in cases with…”
Section: Discussionmentioning
confidence: 99%